Health service utilisation amongst urban Aboriginal and Torres Strait Islander children aged younger than 5 years registered with a primary health‐care service in South‐East Queensland. (17th January 2018) - Hall, Kerry K; Chang, Anne B; Anderson, Jennie; Arnold, Daniel; Otim, Michael; O'Grady, Kerry‐Ann F
Abstract : Aim: The majority of Australia's Aboriginal and/or Torres Strait Islander children live in urban areas; however, little is known about their health service use. We aimed to describe health service utilisation amongst a cohort of urban Aboriginal and/or Torres Strait Islander children aged <5 years. Methods: We analysed health service utilisation data collected in an ongoing prospective cohort study of children aged <5 years registered with an Aboriginal‐owned and operated primary health‐care service. Enrolled children were followed monthly for 12 months, with data on health service utilisation collected at baseline and at each monthly follow‐up. Health service utilisation rates, overall and by service provider and reason for presentation, were calculated and reported as incidence rates per 100 child‐months with the corresponding 95% confidence intervals (CIs). Results: Between February 2013 and November 2015, 180 children were enrolled, and 1541 child‐months of observation were available for analysis. The overall incidence of health service utilisation was 52.5 per 100 child‐months (95% CI 48.7–56.5); 81% of encounters were with general practitioners. Presentation rates were the highest for acute respiratory illnesses (30.7/100 child‐months, 95% CI 27.8–33.9). Conclusions: In this community, acute respiratory illnesses are predominant causes of health service utilisation in young children. The health‐care utilisation profile of these children presents important opportunities for health promotion and intervention.